Bond strength between substrate and post-cast UHPC with innovative interface treatment. (October 2022) - Lu, Kaiwei; Pang, Zhiming; Xu, Qizhi; Yao, Yiming; Wang, Jingquan; Miao, Changwen
Abstract: Ultra-high performance concrete (UHPC) has been utilized in construction joint by virtue of superior strength, crack resistance and durability. However, fiber bridging at the interface between substrate UHPC and post-cast UHPC is limited in current engineering practices, which may lead to the loss of various performances. The objective of the present research is to identify the bond performance of the UHPC-UHPC interface bridged by the steel fibers, using different surface treatment techniques including chipping and steel wire mesh (SWM) pretreatment. To this end, direct tensile tests, direct shear tests and slant shear tests were carried out on the specimens with no treatment, chipping and SWM treatment. The experimental results show that SWM treatment can greatly play the role of fiber bridging at the interface, thus increasing the tensile and shear bond strengths by 55.3% and 333.3%, respectively, compared with interfaces without treatment. The calculation model of the interfacial bond tensile strength and shear strength considering the effect of the fiber bridging was established. Furthermore, conversion of bond tests between tension and shear was discussed, and linear transformation relationship was found among direct tensile tests, direct shear tests and slant shear tests.